2015
DOI: 10.1371/journal.pone.0133483
|View full text |Cite
|
Sign up to set email alerts
|

Up-Down Hand Position Switch May Delay the Fatigue of Non-Dominant Hand Position Rescuers and Improve Chest Compression Quality during Cardiopulmonary Resuscitation: A Randomized Crossover Manikin Study

Abstract: Previous studies have shown improved external chest compression (ECC) quality and delayed rescuer fatigue when the dominant hand (DH) was in contact with the sternum. However, many rescuers prefer placing the non-dominant hand (NH) in contact with the sternum during ECC. We aimed to investigate the effects of up-down hand position switch on the quality of ECC and the fatigue of rescuers during cardiopulmonary resuscitation (CPR). After completion of a review of the standard adult basic life support (BLS) cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A major disadvantage of CCC-CPR is the rapid emergence of fatigue following resuscitation, which reduces the quality of resuscitation (8). Some studies have shown that the number of continuous chest compressions does not decrease despite fatigue, but its efficiency (proper depth) decreases without the rescuer's awareness (9,10). Some scholars have carried out research on addressing the fatigue problem.…”
Section: Continuous Chest Compression Cpr (Ccc-cprmentioning
confidence: 99%
“…A major disadvantage of CCC-CPR is the rapid emergence of fatigue following resuscitation, which reduces the quality of resuscitation (8). Some studies have shown that the number of continuous chest compressions does not decrease despite fatigue, but its efficiency (proper depth) decreases without the rescuer's awareness (9,10). Some scholars have carried out research on addressing the fatigue problem.…”
Section: Continuous Chest Compression Cpr (Ccc-cprmentioning
confidence: 99%